THE HERMENEUTICS OF KHALED M. ABOU EL-FADL AND ITS RELEVANCE WITH RELIGIOUS MODERATION IN INDONESIA - Ansori Ansori (Khazanah: Jurnal Studi Islam dan Humaniora, 2022)
Hermeneutics is an interpretation method that develops in the study of texts. Its usage in the horizon of Islamic text study (Qur’an and Hadith) is not an exception. One figure who discusses different areas of Islamic law is Khaled M. Abou El-Fadl. Khaled has analyzed various texts in Islamic law and their relation to people's lives. This study attempts to explore the thoughts of Khaled M. Abou El-Fadl, especially regarding hermeneutics in analyzing texts and its relation with religious moderation in Indonesia. This study implements the literature review method, where the researcher reviews several works of Khaled M. Abou El-Fadl and other relevant articles. The results of this study reveal that the core problems of authoritarianism in interpretation are the methodological procedural errors of the three elements, namely: the author, text, and reader. The meaning of a text should occur from a complex, interactive, dynamic, and dialectical process between the three elements. Interpreters cannot avoid his subjectivity, therefore an interpreter should fulfill five conditions namely honesty, sincerity, thoroughness, rationality, and self-control. Khaled Abou el-Fadl's hermeneutics is very relevant as a concept of understanding religious teachings to foster and maintain religious moderation, namely mutual understanding between religions and between denominations within a religion.